Bergson fenomenologo - Lanfredini, Roberta (Philosophy Kitchen - Rivista di filosofia contemporanea, 2024)
The aim of the paper is conceived as an initial approach to bring into dialogue the three most important philosophical traditions of the 20th century, specifically Logical Empiricism, Phenomenology and Bergsonism. The implicit theoretical hypothesis, from which the contribution takes its start, is the still not completely explored relation between Bergsonism and Phenomenology. By analysing a shared stronghold of the three traditions, the intuition, and comparing the three solutions to this ‘problem’, an attempt will be made to show how productive a reading of the French philosopher through the lens of phenomenology can be. The analysis of pure experience, as it is presented in Bergson, prefigures the possibility of being understood as a radical phenomenology: more radical than Husserl’s ‘semiotic vision’ and Schlick’s ‘conceptualist vision’.